VOCOWA - VOice COntrolled Wheelchair Autonomous - Madasu S.; Vemula P.K. (My University, 2025)
Project VOCOWA aims to deliver an automated solution for assistive technologies/ advanced smart assistance which will enable elderly and disabled people to live an independent and dignified life. VOCOWA can be implemented using three major technologies i.e., Simultaneous Localization And Mapping (SLAM), Deep Learning and Natural Language Processing to achieve its objectives. As of now the SLAM technology has been implemented successfully. © 2018 Authors.